Conductive composite material

By incorporating low melting point conductors and a compatibilizing agent into conductive composites, the issues of metal leakage and achieving desired mechanical properties are addressed, resulting in electrically conductive and polymer elastic materials suitable for diverse applications.

JP7661019B2Active Publication Date: 2025-04-14THE BOEING CO
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020136254
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-13
Filing Date
2020-08-12
Publication Date
2025-04-14
Estimated Expiration
2040-08-12

AI Technical Summary

Technical Problem

Conductive composites face challenges in achieving sufficient conductivity without metal leakage from the polymer matrix, while also requiring properties like elongation, tensile strength, and thermal stability for various applications.

Method used

The use of low melting point conductors, such as metals and metal alloys with a melting temperature of less than about 60°C, in combination with a compatibilizing agent and optionally a thickener, to create conductive composites that are electrically conductive and polymer elastic.

Benefits of technology

This approach allows for the creation of conductive composites with high metal content that exhibit excellent elasticity and conductivity, preventing metal leakage and enabling a wide range of applications under various environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661019000004
    Figure 0007661019000004
  • Figure 0007661019000005
    Figure 0007661019000005
  • Figure 0007661019000006
    Figure 0007661019000006
Patent Text Reader

Abstract

To provide composites that are conductive, avoid leakage of metal from a polymer, and have characteristics that permit a wide variety of uses under different environmental conditions, i.e., elongation, tensile strength, and thermal stability.SOLUTION: The conductive composites comprise a polymer, a conductor selected from metals and metal alloys, a compatibilizing agent, and an optional thickening agent. The conductive composites of this disclosure are capable of carrying a high metallic content and still exhibit excellent elasticity. The conductive composites are also capable of providing high levels of electrical conductivity using low amounts of a low melting conductor.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to conductive composite materials, and in particular to conductive polymer composite materials and methods and compositions useful for making conductive polymer composite materials. [Background technology]

[0002] A conductive composite, broadly defined, is any composite material that has significant electrical or thermal conductivity. Such composites contain a conductive phase dispersed in a polymer resin. The unique properties of such composites make them technically superior or more cost-effective than alternative materials in a variety of applications. As a result, conductive composites are widely used in fields such as telecommunications, power generation and transmission, defense, aerospace, and medicine.

[0003] In the use of conductive composites, electrical conductivity is usually the primary property of the composite, although it can be significant. The electrical conductivity of conductive composites varies depending on the application. For certain applications, composites with an effective sheet resistance of less than 100 ohms / square are important. Summary of the Invention [Problem to be solved by the invention]

[0004] Conductive composites are generally produced and / or characterized by combining polymeric materials with solid conductive particles. To achieve sufficient conductivity, i.e. to reach percolation, high particle loadings are often required, typically greater than 45% by volume. The polymers used at such particle loadings are typically hard materials. As a result, such particle loadings result in conductive films or coatings with properties such as elongation at break, tensile strength, and thermal stability that make them inadequate or difficult to use. The solution to this problem of employing liquid metals would result in leakage of the metal from the polymer matrix.

[0005] There is also a need for conductive polymer coatings and films that have a wide operating temperature range.

[0006] Thus, there is a need for composite materials that are electrically conductive, do not leach metal from the polymer, and have properties, i.e., elongation, tensile strength, and thermal stability, that allow for a wide range of applications under a variety of environmental conditions. [Means for solving the problem]

[0007] The present disclosure provides an advantageous solution to the problems identified above. In a broad aspect, the present disclosure provides a conductive composite material comprising a polymer, a low melting point conductor, i.e., a conductor selected from metals and metal alloys having a melting temperature below about 60° C., and a compatibilizer. The low melting point conductor and the compatibilizer are typically in a paste form.

[0008] The paste provides (1) electrical conductivity without hardness and (2) increased viscosity and improved flow characteristics to prevent leakage of the low melting point conductor from the composite.

[0009] The present disclosure provides a composite material that is both electrically conductive and polymerically elastic, both of which properties are difficult and often unattainable in a single composite material using common electrical conductivity delivery methods.

[0010] Composite materials that have both polymer elasticity and electrical conductivity are particularly useful in applications where it is desired to reduce or eliminate unwanted electromagnetic interference.

[0011] In another aspect, the present disclosure provides a conductive composite material that includes a polymer, a low melting point conductor, a compatibilizer, and an optional thickener.

[0012] The conductive composite materials of the present disclosure are capable of carrying high metal loadings and still exhibit excellent elasticity.

[0013] Additionally, conductive composites are capable of providing high levels of electrical conductivity using small amounts of low melting point conductors.

[0014] In another aspect, the conductive composite of the present disclosure is in the form of a laminate. The laminate conductive composite includes a continuous layer of a conductive composition, typically a paste, that includes a low melting point conductor and a compatibilizer.

[0015] In another aspect, the conductive composite comprises a conductive network stably and homogeneously and / or continuously entrapped within a polymer matrix, the network including a low melting point conductor and a compatibilizer, in this aspect, the conductor is uniformly or homogeneously distributed throughout the polymer matrix.

[0016] In another aspect, the present disclosure provides a generally paste-like composition comprising a metal or metal alloy having a melting temperature below about 60° C. and a compatibilizer.

[0017] Yet another aspect of the present disclosure is a method for producing a thermally conductive composite material comprising: an elastomer; a conductor selected from metals and metal alloys having a melting temperature of less than about 60° C.; and a compatibilizer; the thermally conductive composite material having a melting temperature of less than about 5×10 at 20° C. 5 An electrically conductive composite material is provided that has or exhibits a maximum bulk conductivity of S / m, an elongation of 50% or greater, and a tensile strength of 3 MPa or greater.

[0018] The present disclosure further provides a conductive composite material comprising an elastomer, a conductor selected from metals and metal alloys having a melting temperature of less than about 60° C., and a compatibilizer.

[0019] The present disclosure also provides a substrate bearing a layer of a conductive composite material comprising a polymer, a conductor selected from metals and metal alloys having a melting temperature below about 60° C., and a compatibilizer.

[0020] The present disclosure provides a method of making a substrate carrying a conductive composite layer, the method comprising heating a conductive composite material disclosed herein and applying the conductive composite material to a substrate.

[0021] In another aspect, the present disclosure provides a method of shielding an electrical component from electromagnetic radiation or electromagnetic interference, the method comprising providing a conductive composite of the present disclosure between a source of electromagnetic radiation and the electrical component.

[0022] The conductive composite materials disclosed herein can be rigid or flexible, and in certain instances, the conductive composite materials have polymeric elastic properties, i.e., are elastomeric.

[0023] The conductive composites of the present disclosure may be manufactured by mixing a liquid metal, typically in a paste form, such as a gallium alloy, with a polymer or prepolymer and optionally curing the prepolymer or polymer.

[0024] The conductive composite may be produced by a method comprising mixing a monomer mixture or polymer composition with a composition comprising a conductor selected from metals and metal alloys having a melting temperature below about 60° C. and a compatibilizer. The method may further optionally comprise curing the mixture to form the conductive composite.

[0025] In another aspect, the conductive composite of the present disclosure may be produced by layering a conductive paste comprising (a) a conductor selected from metals and metal alloys having a melting temperature of less than about 60° C. and (b) a compatibilizer onto a surface of a cured or partially cured first polymer.

[0026] In yet another aspect, the conductive composite of the present disclosure may be produced by applying a conductive paste to a non-sticky surface, overlaying an uncured polymer onto the paste, and then curing the polymer. The composite may then be conveniently removed from the non-sticky surface by peeling it away from the non-sticky surface. After removal from the non-sticky surface, an additional layer of cured or uncured polymer may be added over the conductive paste as needed or desired, and cured to create a sandwich or laminate structure as needed.

[0027] In the conductive composite material disclosed herein, the paste has the following functions: to provide electrical conductivity without unnecessary stiffness, and to improve the viscosity and flow properties of the conductor to prevent leakage during manufacture or use.

[0028] The present disclosure also provides liquid metal pastes that exhibit a loss modulus higher than a storage modulus, i.e., have a tan delta greater than 1, typically comprising a gallium alloy and a compatibilizer. [Brief description of the drawings]

[0029] [Figure 1] 1 is a photograph of a paste applied onto a release film, prepared according to Example 2. The paste is prepared using a gallium alloy containing 61.0 wt. % gallium, 25.0 wt. % indium, 13.0 wt. % tin, and 1.0 wt. % zinc, polyethylene glycol p-(1,1,3,3-tetramethylbutyl)phenyl ether (Triton™ X100), stainless steel powder (as a thickener), and stainless steel wire (as a thickener). [Diagram 2] 1 is a photograph of the laminate composite of Example 2. The conductive composite is a laminate including a layer of paste between layers of polymethylsiloxane (Sylgard™ 184). [Diagram 3] 1 is a series of photographs showing the effect of compression, in the direction of the arrows, on a silicone sponge filled with a gallium alloy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] As used herein, "low melting point conductor" refers to a conductor selected from metals, metal alloys and mixtures thereof having a melting temperature below about 60°C.

[0031] As used herein, "conductive" means capable of conducting electricity or of transmitting an electric current. "Conductivity" refers to the degree to which a particular material conducts electricity. As used herein, "conductor" refers to a material that is electrically conductive, i.e., that conducts electricity.

[0032] As used herein, "substantially non-leaking" means that less than about 10% by volume of the conductor leaks out of the composite at 50% elongation.

[0033] As used herein, "conductive network" refers to an interconnected system capable of transferring electrons between different regions of a composite material, i.e., generating an electric current.

[0034] As used herein, "soft" refers to a material that is not rigid, i.e., a material that bends rather than breaks, and more specifically, a material that has a Young's modulus (E) of less than about 10 gigapascals (GPa). In certain instances, "soft" as used herein refers to a Young's modulus of less than about 2 GPa. In other instances, "soft" as used herein refers to a Young's modulus of less than about 1 GPa.

[0035] "Conductive mixture," "paste," and "paste layer" are used interchangeably herein.

[0036] Thus, as used herein, "stably and homogeneously entrapped within the polymer" means that the conductor and compatibilizer and optional thickener are permanently retained within the polymer matrix and do not migrate or leak within the composite during use of the composite. In this regard, the composite is a substantially homogeneous blend or mixture of the polymer, compatibilizer and optional thickener. The electrical conductivity of the composite does not decay over time.

[0037] Thus, as used herein, "stably and homogeneously entrapped between the polymer layers" means that the conductor and compatibilizer and optional thickener are permanently retained as layers between the polymer layers within the laminate conductive composite and do not migrate or leak within the composite during use of the composite. The electrical conductivity of the laminate composite does not decay over time.

[0038] As noted above, the present disclosure provides a solution to problems previously encountered in producing conductive composites. The conductive composites disclosed herein include a polymer, a low melting point conductor, and a compatibilizer. These conductive composites can be made flexible or rigid depending on the desired application. Importantly, the conductor does not leak, or does not substantially leak, out of the composite when the composite is flexed or otherwise manipulated.

[0039] The conductive composite material in this specification is in the form of a laminate or blend of materials. In the laminate, the low melting conductor and the compatibilizer are a mixture, usually in a paste form, carried on or between polymer layers. The polymer in each layer may be a single polymer material or a mixture of polymer materials. As used herein, the term "conductive mixture layer" refers to a layer of the laminate that contains the low melting conductor and the compatibilizer.

[0040] The thickness of each layer in the laminate, i.e., the polymer layer and the conductive laminate layer, may be adjusted as necessary to achieve the desired properties of the final composite. The laminate composite herein may comprise multiple polymer layers and multiple conductive layers. For example, the laminate may comprise a total of five layers, with each of the three polymer layers sandwiching a conductive mixture, i.e., the three polymer layers are separated by a conductive mixture layer (paste layer) except at the edges of the composite where the polymer layers are in contact with each other. In an example of a three-layer laminate, i.e., a composite in which a conductive mixture layer is sandwiched between two polymer layers, each polymer layer may be about 1 mm thick, with the total laminate thickness being 5 mm. The conductive mixture layer in such a configuration may be about 3 mm thick. In another example of a three-layer laminate, each polymer layer may be about 2 mm thick, with the conductive mixture layer being about 1 mm thick. When weight reduction is important, the composite will include fewer layers, with each layer being as thin as possible while still providing the desired level of conductivity.

[0041] Forming the conductive composite as a laminate with successive layers of the conductive composition allows for the use of less of the low melting point conductor and compatibilizer to obtain the desired level of conductivity.

[0042] When used for shielding, the conductive composites of the present disclosure manufactured as laminates are preferred for use with flat parts or parts having a single axis of curvature, such as cylinders, etc. Laminates can be used to shield parts with complex surface geometries, but are less commonly used in such situations due to their tendency to collapse when applied or wrapped around complex surfaces.

[0043] In another example, the conductive composite is a blend or mixture that includes a conductor and a compatibilizer, which are substantially uniformly distributed throughout the polymer. Such composites can be produced by mixing a monomer mixture or polymer composition with the low melting conductor and the compatibilizer, and optionally curing the polymer or polymerizing the monomer mixture. In such conductive composites, the low melting conductor and the compatibilizer are substantially uniformly distributed throughout the polymer.

[0044] The conductive composites disclosed herein, in blends or mixtures, comprise a conductive network that is stably and homogeneously and / or continuously entrapped within the polymer. The network comprises a low melting conductor, i.e., a conductor having a melting temperature below about 60° C., and a compatibilizer. A compatibilizer is a compound or metal that does not alloy with the conductor when present in the composite or during manufacture.

[0045] Also, without wishing to be bound by theory, it is believed that in composites that are blends of low melting conductors and polymers (i.e., other than laminates), the metal and compatibilizer form a conductive network inside the pores (free volume) that are generated in the polymer during curing. Furthermore, without wishing to be bound by theory, it is believed that the pore structure of the polymer can be considered open, thereby allowing connectivity between different regions of the composite. The compatibilizer works with the low melting conductor and optional thickener to hold the conductor within the pores. The combination of the compatibilizer and conductor can be considered a paste. As will be described below, the paste behaves more like a liquid than a solid, allowing the composite to be flexible, e.g., bendable. Using a conductor with a melting temperature of less than about 60° C. allows the formation of a paste and the formation of a conductive network.

[0046] The conductive composites of the present disclosure, produced as blends of polymers, low melting conductors, compatibilizers, and optional thickeners, can be used, for example, as conductive seals or coatings for a variety of surfaces and materials.

[0047] The conductive composites of the present disclosure, fabricated as blends of polymers, low melting conductors, compatibilizers, and optional thickeners, are particularly suitable for use as shields for parts having complex surface geometries, as such composites are able to conform to complex surface geometries without collapsing.

[0048] In certain examples, the conductive composites of the present disclosure can be made to include abundant conductive paths. "Abundant conductive paths" refers to electrical pathways with three-dimensional electrical connections. As described elsewhere herein, the conductive composites of the present disclosure made as blends of polymer, low melting point conductor, compatibilizer, and optional thickener contain a network of low melting point conductor and compatibilizer stably and homogeneously and / or continuously trapped within the polymer matrix. As a result, the conductor is uniformly or homogeneously distributed in three dimensions throughout the polymer matrix, thereby forming abundant conductive paths. Bending or folding the blended conductive composites does not usually result in loss of conductivity across the bend or fold, since there is still another electrical path around the compression point caused by the bend or fold.

[0049] As mentioned above, the present disclosure provides a conductive composite material that includes a polymer, a low melting point conductor, and a compatibilizer. The low melting point conductor and the compatibilizer are typically in a paste form, i.e., a viscous mixture of the components.

[0050] The polymer may be a rigid polymer or an elastomer. The rigid or elastomeric polymer herein may be a thermoset or thermoplastic elastomer. Whether the polymer selected to make the conductive composite is rigid or elastomeric usually depends on the end use or application method for applying the composite to a substrate. For example, if the end use requires flexibility, the polymer is elastomeric so that the conductive composite is flexible. In such a situation, the composite is referred to as a soft conductive composite. Thermoplastic elastomers are useful for manufacturing methods that require the conductive composite to be molded or shaped into a desired configuration or applied to a substrate.

[0051] Thermoset elastomers useful for making the conductive composites disclosed herein include acrylics, polyesters and vinyl esters, phenolic resins, amine functional resins, polyamides such as nylon, polylactic acid, polystyrene, acrylonitrile-butadiene-styrene, polybenzimidazole, polycarbonate, polyethersulfone, polyaryletherketone, polyetherimide, polyurethane, polyurea / polyurethane hybrids, polyimides, polysulfides, furan resins, copolymers thereof, mixtures thereof, and the like.

[0052] Thermoset elastomers can also be made from epoxy-functional resins, which can be homopolymerized using anionic or cationic catalysts and heat, or copolymerized via nucleophilic addition reactions with multifunctional crosslinkers, also known as curing agents.

[0053] In a particular example, the conductive composite is optionally flexible and is formed from a thermoplastic polymer, e.g., a thermoplastic elastomer, such as, for example, polyamides such as nylon, polylactic acid, polystyrene, acrylonitrile-butadiene-styrene, polybenzimidazole, polycarbonate, polyethersulfone, polyoxymethylene, polyaryletherketone, polyetherimide, polyethylene, polypropylene, polyphenylene oxide, polyphenylene sulfide, polyvinyl chloride, polyester, polyvinylidene fluoride, polysiloxane, silicones such as polyfluorosiloxane, perfluoropolyether, polybutadiene, polyacrylate, polyurethane, polyurea / polyurethane hybrid, thermoplastic vulcanizate, polytetrafluoroethylene (Teflon), polyepoxide, polyimide, cyanate ester, polycyanurate, polysulfide, copolymers thereof, mixtures thereof, and the like.

[0054] The viscosity of suitable thermoplastic elastomers used in producing the conductive composites disclosed herein is about 1000 to about 100,000 cP, about 1000 to about 25,000 cP, about 25,000 to about 50,000 cP, about 50,000 to about 75,000 cP, or about 75,000 to about 100,000 cP under typical processing conditions. In a particular example, the viscosity of suitable thermoplastic elastomers used herein is about 1000 to about 50,000 cP under typical processing conditions. As used herein, "typical processing conditions" include about room temperature (about 25°C) to about 200°C, or about room temperature to about 100°C. Such thermoplastic elastomers are advantageous for producing soft materials.

[0055] The compositions and methods disclosed herein employ low melting point conductors. Suitable low melting point conductors are metals and metal alloys that have a melting temperature of less than about 60° C. In certain examples, the melting point of the low melting point conductor is less than about 50° C., less than about 40° C., less than about 30° C., less than about 25° C., or less than about 20° C. In certain examples, the melting point is low enough that the alloy is liquid when initially mixed with the compatibilizer, and low enough that it forms a spreadable paste when thoroughly mixed with the compatibilizer.

[0056] In a particular example, the low melting point conductor is an alloy containing at least about 50% by weight of gallium, bismuth, mercury, or a combination thereof. A suitable gallium alloy further contains indium, tin, bismuth, phosphorus, lead, zinc, cadmium, antimony, or a combination thereof. Indium, tin, bismuth, phosphorus, lead, zinc, cadmium, antimony, or a combination thereof may be included to modify the melting temperature of the alloy, if desired.

[0057] The low melting point conductor may contain small amounts of impurities, i.e., amounts that do not substantially alter the rheological properties of the paste or the conductive and mechanical properties of the final conductive composite.

[0058] In one example, the low melting point conductor used in the conductive composite material disclosed herein is an alloy containing indium and 50-97% by weight gallium.

[0059] In another example, the low melting conductor used to form the conductive composites disclosed herein is an alloy containing about 15-30% by weight indium, about 55-80% by weight gallium, and at least one metal selected from tin and zinc. A suitable gallium alloy is commercially available from Indium Corporation.

[0060] Representative gallium alloys for use in the disclosed compositions include alloys having the following compositions and properties:

[0061] [Table 1]

[0062] The low melting conductor may be selected to achieve appropriate properties of the paste composition used to make the composite. The paste composition is preferably homogenous and made with the low melting conductor and a compatibilizer. The paste is typically anhydrous. Water is not required and is typically avoided when making the paste.

[0063] Compatibilizers for use in the conductive composites herein include non-ionic amphiphilic compounds, ionic amphiphilic compounds, metal nanoparticles, mixtures thereof, and the like.

[0064] The paste can be prepared, for example, by mixing the low melting conductor, the compatibilizer, and optional ingredients using a centrifugal planetary mixer. The resulting paste can be stored for future use.

[0065] The compatibilizer used herein unexpectedly improves the processability (e.g., flowability, ease of application, etc.) of the paste. Without wishing to be bound by theory, it is believed that mixing the compatibilizer with the low melting conductor forms a coating of the compatibilizer on the surface of the particles or droplets of the low melting conductor, thereby lowering the surface energy of the low melting conductor. Furthermore, again without wishing to be bound by theory, it is believed that the compatibilizer forms a layer or layers on the droplets of the low melting conductor to reduce or prevent oxidation of the conductor, but does not produce a shell of the type obtained by using an acid.

[0066] In certain instances, the compatibilizers used herein may be used to thicken the paste, i.e., to increase the viscosity of the paste.

[0067] Additionally, compatibilizers may be added to reactivate the paste if oxidation occurs on the metal surface. As used herein, "reactivate" means that a separated mixture of compatibilizer and low melting conductor can be returned to a homogenous paste state by introducing additional compatibilizer and subjecting the mixture to suitable shear conditions as described below.

[0068] In instances where the paste includes particles of thickener, as described elsewhere herein, it is believed that the disclosed compatibilizer allows for penetration into the pores or voids formed between the particles of the thickener. Without being bound by theory, it is believed that the compatibilizer promotes penetration by reducing the viscosity of the liquid materials in the paste. It is believed that penetration into the pores allows for the use of conductors with lesser melting points and provides homogeneity to the paste.

[0069] In particular examples, the paste used to form the conductive composite contains a low melting conductor and a compatibilizer in a weight ratio of low melting conductor to compatibilizer of about 5:1 to 50:1, about 10:1 to 30:1, about 15:1 to 25:1, or about 20:1 to 25:1. Thus, the amount of compatibilizer as a percentage of the low melting conductor ranges from about 2% to about 20% by weight. Particularly useful amounts of compatibilizer as a percentage of the low melting conductor range from about 4% to 10% by weight. Phase separation should be avoided. At higher concentrations of compatibilizer, phase separation may occur, which can be addressed by using thickeners of the type disclosed elsewhere herein.

[0070] In a particular example, the compatibilizer comprises inorganic nanoparticles, such as metal nanoparticles, with a linear dimension of less than 100 nm, less than about 90 nm, less than about 80 nm, less than about 70 nm, less than about 60 nm, less than about 50 nm, less than about 40 nm, less than about 30 nm, or less than about 20 nm. Suitable nanoparticles include metals that are insoluble, i.e., do not dissolve, in low melting conductors. Suitable metals for use as nanoparticles are those in which the solubility of gallium in the metal at room temperature is less than 5 mole %. Examples of suitable metals for use as nanoparticle compatibilizers herein include copper, nickel, stainless steel, tin, titanium, tungsten, mixtures thereof, alloys thereof, and the like.

[0071] In a particular example, the compatibilizer is a non-ionic amphiphilic compound or a mixture of non-ionic amphiphilic compounds. Examples of suitable non-ionic amphiphilic compounds include fatty alcohol alkoxylates such as fatty alcohol ethoxylates, alkylphenol alkoxylates such as alkylphenol ethoxylates, fatty acid alkoxylates such as fatty acid ethoxylates, alkoxylated amines such as ethoxylated amines, fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, alkyl polyglucosides, fatty amine oxides, sulfoxides, organic phosphine oxides, mixtures thereof, and the like.

[0072] In a particular example, the compatibilizer is an ionic compound. Suitable ionic amphiphilic compounds include anionic compounds and cationic compounds. Representative anionic compounds are alkyl sulfates, alkyl ether sulfates, alkyl sulfonates, alkyl ether sulfonates, alkyl phosphates, and alkyl carboxylates. Representative cationic compounds are quaternary ammonium compounds, monoalkyl ammonium salts, dialkyl ammonium salts, and trialkyl aluminum salts.

[0073] The selection and amount of the particular anionic compound (or mixtures thereof) or cationic compound (or mixtures thereof) used to form the conductive paste will depend on the particular polymer used to make the conductive composite. The type and amount of anionic or cationic compound is selected to avoid degradation or depolymerization of the polymer.

[0074] In a particular example, the compatibilizer is a surfactant.

[0075] In a particular example, the compatibilizer is a non-ionic amphiphilic compound or a mixture of non-ionic amphiphilic compounds. Particularly useful non-ionic amphiphilic compounds are alkylphenol ethoxylates. Representative alkylphenol ethoxylates are octophenol ethoxylates such as Triton® X-100 (polyethylene glycol p-(1,1,3,3-tetramethylbutyl)phenyl ether with an average of 9.5 ethylene oxide units) and nonylphenol ethoxylates.

[0076] Other particularly useful nonionic amphiphilic compounds are the poloxamers, which are triblock copolymers of poly(ethylene oxide)·poly(propylene oxide)·poly(ethylene oxide) (PEO-PPO-PEO).

[0077] In certain instances, the conductive composite also includes an optional thickener. In use, the thickener is typically mixed with the low melting point conductor and the compatibilizer, resulting in a paste or conductive mixture layer.

[0078] The thickeners used herein function as viscosity modifiers and can help inhibit or minimize flow of the low melting conductor in the paste. The thickeners used herein can be inorganic or organic materials. The thickeners do not dissolve the conductor or otherwise form a solution with the conductor, remain solid when mixed with the conductor, and are not wetted by the conductor. The thickeners are typically used as particles, e.g., rod-shaped, linear, substantially spherical particles, or mixtures thereof, and the particle size determines the ease with which the powder can be homogenized with the conductor to form a paste. Typically, thickeners with a larger surface area are better thickeners than those with a smaller surface area. The combination of the thickener with the conductor, e.g., gallium alloy, is selected to provide adequate wetting of the thickener and adequate flowability or elasticity of the paste. The particle size and amount are selected to produce a paste composition with a tan delta value higher than 1, i.e., a paste that behaves more like a liquid than a solid, making the resulting composite soft.

[0079] In certain instances, the thickener comprises inorganic thickener particles, such as rod-shaped or linear particles, that have an aspect ratio of greater than 2, i.e., the length is at least twice as long as the width. The aspect ratio can be measured using a microscope.

[0080] In a particular example, the thickener comprises substantially spherical particles of an inorganic thickener having an average particle size of about 0.1-500 μm (100-500,000 nm). Particles in this size range have sufficient surface area to function as a thickener to form a paste with the conductor. In a particular example, the thickener comprises substantially spherical particles of an inorganic thickener having an average particle size of about 1-25 μm, about 25-50 μm, about 50-75 μm, about 75-100 μm, about 100-150 μm, about 150-200 μm, about 200-250 μm, about 250-300 μm, about 300-350 μm, about 350-400 μm, or about 450-500 μm. In another example, the thickener comprises substantially spherical particles of an inorganic thickener having an average particle size of about 50-150 μm. A particular example is particles of inorganic thickeners having an average particle size of about 0.1-5 μm.

[0081] In one example, the thickener is an inorganic thickener comprising rod-shaped or filamentary particles having an aspect ratio greater than 2 and a length of about 0.01-10 mm. In particular examples, the length of the rod-shaped particles of the inorganic thickener is about 0.01-0.5 mm, about 0.05-10 mm, about 0.01-10 mm, about 0.01-0.1 mm, about 0.1-1 mm, about 1-5 mm, or about 5-10 mm. The use of rod-shaped or filamentary particles contributes more to the electrical conductivity of the final composite than do nearly spherical particles. As a result, the amount of paste required to achieve a given electrical conductivity can be reduced. The reduction in the amount of paste used to produce the composite can be achieved by reducing either the amount of conductor or the amount of thickener.

[0082] In certain examples, the inorganic thickener comprises a mixture of rod-shaped or filamentary particles and substantially spherical particles, or a mixture of rod-shaped, filamentary, and substantially spherical particles.

[0083] In a particular example, the thickener comprises particles of an organic thickener having an average particle size of about 0.1-500 μm. In a particular example, the thickener comprises particles of an organic thickener having an average particle size of about 1-25 μm, about 25-50 μm, about 50-75 μm, about 75-100 μm, about 100-150 μm, about 150-200 μm, about 200-250 μm, about 250-300 μm, about 300-350 μm, about 350-400 μm, or about 450-500 μm. In a particular example, the thickener comprises particles of an organic thickener having an average particle size of about 50-150 μm. In a particular example, the organic thickener comprises particles of an organic thickener having an average particle size of about 0.1-5 μm.

[0084] In those instances where the paste further comprises a thickening agent, the thickening agent may be used in an amount to produce the appropriate viscosity and / or to adjust the conductive properties of the paste and the resulting composite. A suitable concentration of the inorganic thickening agent in the paste ranges from about 0.1% to 20% by weight of the paste composition. A suitable concentration of the organic thickening agent in the paste ranges from about 0.1% to 40% by weight of the paste composition.

[0085] A suitable amount of thickener by volume in the paste composition ranges from about 5 to 50% by volume of the paste. In particular examples, the amount of thickener is about 5 to about 10%, about 5 to about 15%, about 10 to about 20%, about 15 to about 25%, about 20 to about 30%, about 25 to about 35%, or about 30 to about 45% by volume of the paste composition. Such amounts are advantageous for producing paste compositions with tan delta values ​​higher than 1, i.e., pastes that behave more like a liquid than a solid, making the resulting composite soft.

[0086] As mentioned above, the amount of thickener can be reduced when rod-shaped or filamentary particles are used as the thickener. A suitable amount of rod-shaped or filamentary particle thickener in the paste is in the range of about 2 to 40% by volume of the paste. In a specific example, the amount of thickener is about 2% to about 5%, about 5 to about 10%, about 10 to about 15%, about 15 to about 20%, about 20 to about 25%, about 25 to about 30%, or about 30 to about 40% by volume of the paste composition.

[0087] Suitable electrical conductivity can be achieved in the conductive composites disclosed herein without employing a large amount of solid conductive particles in the paste, i.e., without a loading of more than about 45% by volume of solid conductive particles. However, in certain instances, loadings of metal particles in the paste of more than 45% by volume may be employed when insufficient metal is present in the liquid phase to form a desired level of electrical connection between the metal particles. Thus, if necessary, particle loadings of more than 45% by volume, for example between about 45% and 80% by volume, may be used in the paste.

[0088] In a particular example, the thickener used to make the conductive composite is an organic thickener. Suitable organic thickeners include compounds with a melting point above 60°C, i.e., a temperature that does not cause the thickener to fuse with the alloy before or during the manufacture of the composite. Examples of such compounds include maltol, phenol, naphthalene, 1-naphthol, 2-naphthol, 4-pyridone, and carbon, such as graphite and carbon black. If the organic thickener is a compound with a phenolic hydroxyl group, the compound may react with the isocyanate group of the diisocyanate or polyisocyanate through the hydroxyl group, but the reaction will be slower than a urethane- or urea-forming reaction. When used appropriately, such compounds can be used to modify the properties of the resulting polymer. Alternatively, the organic thickener may be graphite or carbon particles.

[0089] In a particular example, the thickener is an inorganic thickener or a combination of inorganic thickeners. Suitable inorganic thickeners include metal oxides such as titanium dioxide, zinc oxide, metals with melting points above 60°C, and ceramic materials. In the case of metals, those with melting points above 60°C are selected to prevent the thickener from melting before or during the manufacture of the composite. Suitable metals include nickel; metal oxides of nickel, titanium, tungsten, stainless steel, copper, tin and zinc; ceramics; and combinations thereof.

[0090] The conductive composite material disclosed herein includes about 0.1 to about 50% by volume of the conductor. The amount of the conductor depends on the intended use of the composite material and the type and amount of other conductors in the composite material. In general, when no other conductors are included, a higher percentage of the conductor is required to increase the electrical conductivity. Of course, if the conductor has a relatively high electrical conductivity, a smaller conductor volume may be used. In certain examples, the conductive composite material includes about 0.1 to about 30%, about 0.1 to about 20%, or about 0.1 to about 10% by volume of the conductor. In other examples, the conductive composite material includes about 0.5 to about 30%, about 0.5 to about 20%, or about 0.5 to about 10% by volume of the conductor. In still other examples, the conductive composite material includes about 1 to about 30%, about 1 to about 20%, or about 1 to about 10% by volume of the conductor. In yet other examples, the conductive composite comprises about 5 to about 30%, about 5 to about 20%, or about 5 to about 10% conductor by volume. In particular examples, the amount of thickener is about 2 to about 10%, about 1 to about 5%, about 2 to about 5%, about 5 to about 15%, about 10 to about 20%, about 15 to about 25%, about 20 to about 30%, about 25 to about 35%, or about 30 to about 45% by volume of the composite.

[0091] The thickener may be a mixture of at least one organic thickener and at least one inorganic thickener. The mixture of organic and inorganic thickeners can be used to modify the flow or elasticity of the paste.

[0092] In a particular example, the thickener comprises rod-shaped particles, linear particles, substantially spherical particles or mixtures thereof, wherein the rod-shaped particles, linear particles and substantially spherical particles comprise a metal selected from nickel, titanium, tungsten, stainless steel, copper and tin, a metal oxide of nickel or zinc, ceramics, or a combination thereof, wherein the substantially spherical particles have an average particle size of about 0.1-500 μm (100-500,000 nm) and the rod-shaped particles and linear particles have a length of 0.01-10 mm.

[0093] The present disclosure provides a paste composition comprising a metal or metal alloy, e.g., a low melting point conductor, having a melting temperature below 60° C., a compatibilizer, and optionally one or more thickeners. In another example, the paste composition comprises a metal or metal alloy, having a melting temperature below 60° C., a compatibilizer, and at least one thickener selected from organic and inorganic thickeners.

[0094] In certain examples, the paste compositions disclosed herein and useful for making conductive composites may have a loss modulus (G'') that is higher than the storage modulus (G'), i.e., a tan delta value greater than 1. Thus, the paste compositions of the present disclosure behave more like a liquid than a solid. The paste compositions of the present disclosure have a viscosity of 500-100,000 Pa.s at 1 Hz, as measured using a dynamic shear rheometer according to ASTM D7175.

[0095] The conductive composite material disclosed herein is prepared by mixing the above-mentioned components to form an intermediate composition. (i) a paste comprising a low melting point conductor, a compatibilizer, and an optional thickener; (ii) a monomer mixture; It can be prepared by mixing.

[0096] After mixing these materials, the resulting intermediate composition may be cured to form a composite material. Depending on the choice of starting materials, the composite material may be rigid or flexible. The composite material may be thermoplastic, i.e., flexible when heated.

[0097] Alternatively, the conductive composite material disclosed herein comprises: (i) a paste comprising a low melting point conductor, a compatibilizer, and an optional thickener; (ii) a polymer or a polymer mixture; It can be prepared by mixing.

[0098] Optionally, after mixing these materials, the polymer is cured to form a composite material. Depending on the choice of starting materials, the composite material will be hard or soft. The composite material may be thermoplastic, i.e., soft when heated.

[0099] The laminate composite of the present disclosure can be made by layering a conductive paste comprising (a) a conductor selected from metals and metal alloys having a melting temperature below about 60° C. and (b) a compatibilizer on a surface of a first polymer, and optionally applying a layer of a second polymer onto the conductive paste. The second polymer can be the same type as the first polymer or a different type. The addition of the second polymer layer encapsulates the conductive paste.

[0100] The laminate conductive composite of the present disclosure can also be made by applying a conductive paste to a non-sticky surface, overlaying an uncured polymer onto the paste, and then curing the polymer. The composite can then be conveniently removed from the non-sticky surface by peeling it off. If desired, a second polymer (which may be the same type as the first polymer or a different type) can be optionally applied onto the conductive paste. The addition of the second polymer layer encapsulates the conductive paste.

[0101] The non-stick surface may be any suitable non-stick material, examples of suitable non-stick materials include polytetrafluoroethylene, anodized aluminum, ceramics, and enameled cast iron.

[0102] The conductive composites disclosed herein may further include additional materials to impart other properties to the composites. For example, a thermo-oxidative stabilizer (a material or additive that improves thermo-oxidative stability) may be included in either the polyol, the diisocyanate or polyisocyanate, or the paste composition prior to forming the composite. Depending on the properties required for the composite and the environment in which the composite will be used, the thermo-oxidative stabilizer may be phosphorus, iron oxide, phenolic antioxidant, metal passivator, or a combination thereof. Adding a thermo-oxidative stabilizer to the conductive composites disclosed herein extends the operating temperature range of the composite.

[0103] Suitable metal passivators include nitrates such as nitric acid, citrates such as citric acid, tungstates, molybdates, chromates, mixtures thereof, and the like.

[0104] The sheet resistance of a particular conductive composite will depend on the end use application, for example, if the composite is to be used to shield electrical components from electromagnetic radiation, e.g., to minimize electromagnetic interference that may disrupt or interfere with sensitive electronic equipment, a minimum sheet resistance of less than 100 ohms / square is preferred.

[0105] In a particular example, the conductive composite material disclosed herein has a thermal conductivity of about 5×10 5 Indicates the maximum bulk conductivity in S / m.

[0106] In certain instances, the conductive composites disclosed herein exhibit an elongation of 50% or greater.

[0107] In other examples, the conductive composites disclosed herein exhibit a tensile strength of 3 MPa or greater.

[0108] In a particular example, the conductive composite material disclosed herein has a thermal conductivity of about 5×10 5 It exhibits a maximum bulk conductivity of 1.0 S / m, an elongation of more than 50%, and a tensile strength of more than 3 MPa.

[0109] In certain examples, the conductive composite materials disclosed herein include An elastomer; A low melting point conductor; and a compatibilizer; At 20°C, approximately 5 x 10 5 It has a maximum bulk conductivity of S / m, an elongation of 50% or more, and a tensile strength of 3 MPa or more.

[0110] Sheet resistance is a standard measurement and can be determined using a four-point probe.

[0111] In certain examples, the conductive composite is soft and has an elongation of greater than about 50%. In other examples, the conductive composite is soft and has an elongation of greater than about 10%, greater than about 20%, greater than about 30%, or greater than about 40%. The soft conductive composite of the present disclosure preferably includes a thermoplastic elastomer. In one example, the thermoplastic elastomer is a thermoplastic polyurethane.

[0112] In certain instances, the conductive composite has an elongation of greater than about 50%. In other instances, the conductive composite has an elongation of greater than about 10%, greater than about 20%, greater than about 30%, or greater than about 40%.

[0113] In certain examples, the conductive composite material is soft and has a tensile strength of 3 MPa or more. In certain examples, the conductive composite material is soft. In certain examples, the conductive composite material has a tensile strength of 3 MPa or more.

[0114] In certain examples, the conductive composite has a density of about 2-10 g / mL. In other examples, the conductive composite has a density of about 10-20 g / mL. In yet other examples, the conductive composite has a density of about 1-5 g / mL or about 3-8 g / mL. In one example, the conductive composite has a density of less than 7 g / mL. This parameter can be readily measured by determining the mass of a known volume or by measuring the volume of water displaced by a known mass.

[0115] The present disclosure further provides products, articles, and structures comprising a substrate carrying a layer of the conductive composite material disclosed herein, and in certain instances, the soft conductive composite material disclosed herein. Such products, articles, and structures can be made by heating and applying the thermoplastic or thermoset conductive composite material disclosed herein to the substrate.

[0116] The conductive composite material disclosed herein can be produced as follows.

[0117] The paste composition is prepared by combining the low melting point conductor and the compatibilizer and kneading the resulting mixture sufficiently to form a homogenous paste. Kneading can be performed using a shear mixer at about 25-2500 rpm. In particular examples, the shear kneading to form the paste composition is performed at about 25-125 rpm, about 125-250 rpm, about 250-400 rpm, about 400-700 rpm, about 700-1500 rpm, or about 1500-2500 rpm. Alternatively, kneading can be performed using a centrifugal planetary mixer. The resulting paste may be stored for future use.

[0118] In a particular example, the conductive composite of the present disclosure can be produced by layering a conductive paste comprising (a) a conductor selected from metals and metal alloys having a melting temperature below about 60° C. and (b) a compatibilizer onto a surface of a first polymer. The second polymer can be of the same type or a different type than the first polymer.

[0119] Working Example material source Krasol® LBH-P2000 was obtained from Cray Valley and used untreated. Desmophen® NH-1220 was purchased from Covestro and used untreated. Gallium alloy (Indalloy 46L) was purchased from Indium Corporation and used untreated. Maltol, titanium powder (particle size approximately 100 mesh), 4,4'-methylenebis(cyclohexyl isocyanate), isomer (HMDI) mixture and dibutyltin dilaurate (DBTDL) were purchased from Sigma Aldrich and used untreated. Stainless steel wire (3 mm x 2 μm) was purchased from Intramicron and used untreated. Polydimethylsiloxane (Sylgard™ 184) was purchased from Dow Corning and used untreated. Stainless steel powder (type 316, 325 mesh (44 μm)) was purchased from Atlantic Equipment Engineers and was washed with acetone before use.

[0120] The volume percentage of gallium, a low melting point conductor, was determined by back-calculating the percentage of gallium alloy in the composite after sample fabrication.

[0121] Example A: Preparation of Polyurethane Prepolymer (Part A) In a round bottom flask equipped with a nitrogen inlet and an overhead stirrer (Teflon shaft and blade) was added hydroxyl-terminated polybutadiene (Krasol® LBH-P2000, M n=Add 100 g / mol (2100 g, 50.00 g, 23.8 mmol) and HMDI (19.65 g, 74.89 mmol). Place the flask in an oil bath at 100 °C and stir at 175 rpm for 10 minutes. Then add DBTDL (500 ppm) catalyst to the solution using a micropipette and allow the reaction to proceed for 2 hours to form the prepolymer (Part A). Pour the neat Part A (without solvent) into a glass bottle and store it for future use.

[0122] Comparative example C-1 Preparation of paste 18.51 g of a gallium alloy (Indalloy® 46L) and 3.02 g of maltol (a thickener) are mixed for about 5 minutes using a shear mixer at a rotation speed of 100 rpm or less.

[0123] Preparation of a composite containing 21.8% by volume of gallium alloy (paste): Part A (7.64 g) is mixed with gallium alloy-maltol paste (21.53 g) in a shear mixer at 100 rpm or less for approximately 5 minutes. NH1220 (2.56 g) is added to the resulting homogeneous mixture and hand-mixed with a spatula for 1 minute. The mixture is then transferred to a Teflon mold and a thin film is cast using a blade applicator.

[0124] Comparative example C-2 Preparation of paste 27.23 g of gallium alloy (Indalloy® 46L) and 5.86 g of titanium powder (thickener, approximately 100 mesh) are mixed in a shear mixer at a rotation speed of 100 rpm or less for approximately 5 minutes.

[0125] Preparation of a composite material containing 27.8% by volume of gallium alloy (paste) Part A (8.15 g) is mixed with the gallium alloy-titanium paste (33.09 g) in a shear mixer at 100 rpm or less for several minutes. NH1220 (2.73 g) is added to the resulting homogeneous mixture and hand-mixed with a spatula for 1 minute. The mixture is then transferred to a polytetrafluoroethylene (PTFE) mold (e.g., Teflon® brand PTFE) and a thin film is cast using a blade applicator.

[0126] Comparative example C-3 Preparation of paste 29 g of gallium alloy (Indalloy® 46L) and 5.17 g of titanium powder (thickener, approx. 100 mesh) are mixed in a shear mixer at a rotation speed of 100 rpm or less for approximately 5 minutes. Then, stainless steel wire (0.52 g, 3 mm × 2 μm) is added to the paste and mixed under the same conditions.

[0127] Preparation of a composite containing 29.1% by volume of gallium alloy (paste): Part A (8.13 g) is mixed with the gallium alloy-based paste (34.69 g) using a shear mixer at a speed of 100 rpm or less for a few minutes. NH1220 (2.73 g) is added to the resulting homogeneous mixture and hand-mixed with a spatula for 1 minute. The mixture is then transferred to a Teflon mold and cast into a thin film, i.e., 1-2 mm thick, using a blade applicator.

[0128] Comparative example C-4 Silicone sponge containing gallium alloy Preparation of silicone sponge Prepare a silicone sponge essentially according to the procedure described by Liang et al. in J. Mater. Chem. C, 2017, 5(7), pp. 1586-1590, as follows.

[0129] 20 g of part A and 2 g of part B of Sylgard® are mixed using a centrifugal mixer at 2300 rpm for 30 seconds, and then 4 sugar cubes are immersed in the mixture. The sugar cubes containing the polydimethylsiloxane (PDMS) mixture are then placed in a desiccator and degassed under vacuum for about 2 hours. The sugar cubes containing the PDMS mixture are then cured at 65°C for 3 hours. The PDMS on the surface is then wiped off to expose the sugar. The sugar is then immersed in water at 60°C and dissolved under stirring. The PDMS sponge is obtained by drying at 100°C for 2 hours.

[0130] Preparation of a sponge containing approximately 53% by volume of a gallium alloy Cut one silicone sponge in half and immerse it in 15 g of gallium alloy. Then, place the container in a desiccator. Using a vacuum, fill the PDMS sponge with the gallium alloy liquid metal for about 60 minutes.

[0131] The effect of compression on the gallium alloy-filled silicone sponge is shown in Figure 3. As shown in Figure 3, upon compression, the gallium alloy leaks out of the silicone sponge as liquid metal droplets, and after compression, only about 23% by volume of the gallium alloy remains in the silicone sponge. This amount is determined by weighing the sponge before and after compression.

[0132] Comparative example C-5 Nusil™ LSR-5860 Liquid Silicone Rubber Control Preparation of membranes 10 g of Nusil™ LSR-5860 Liquid Silicone Rubber Part A and 10 g of Nusil™ LSR-5860 Liquid Silicone Rubber Part B were mixed with a FlackTek® centrifugal planetary mixer at 2300 rpm for 1 minute. 10 g of tetrahydrofuran (THF) was added to the mixture, and the mixture was mixed by hand with a spatula for several minutes until the mixture was completely dissolved in the THF, after which the mixture was mixed again with a FlackTek® mixer at 2300 rpm for 1 minute. The resulting homogenous mixture was poured onto a release film and cast with a glass rod. The thin film was then heat cured at 100° C. for 2 hours after most of the THF solvent had evaporated (approximately 18 hours / overnight).

[0133] Comparative example C-6 Sylgard™ Control Film Preparation: 10 g of Sylgard™ 184 Part A and 1 g of Sylgard™ 184 Part B were mixed in a FlackTek® centrifugal planetary mixer at 2300 rpm for 1 minute. The mixture was poured onto a release film and cast with a glass rod. The film was heat cured at 100° C. for 45 minutes.

[0134] Example 1 Preparation of paste 60.13 g of gallium alloy (Indalloy® 46L) and 3 g of Triton™ X100 were mixed in a FlackTek centrifugal planetary mixer at 2300 rpm for 1 minute. 6.63 g of stainless steel powder (thickener, 325 mesh (44 μm)) was added to the paste and mixed under the same conditions.

[0135] Fabrication of laminated composites containing 15.5% by volume (paste) of gallium alloy. A thin Nusil 5860 film was produced using the film preparation procedure described in Comparative Example C-5. Once the film was cured, 1 g of the gallium-based paste prepared above in this example was uniformly applied onto the 1.5" x 1.5" cured film. After repeating the film preparation of Comparative Example C-5, 5 g of a mixture of Nusil 5860 Part A and Part B was dissolved in 5 g of THF. The resulting polymer solution was cast onto the gallium-based paste and thermally cured at 100°C for 2 hours after most of the THF solvent had evaporated (approximately 18 hours / overnight). The resulting product was a 1.5" x 1.5" laminated film composite.

[0136] Example 2 Preparation of paste 75.21 g of gallium alloy (Indalloy® 46L) and 3.21 g of Triton™ X100 were mixed in a FlackTek centrifugal planetary mixer at 2300 rpm for 1 minute. 5.45 g of stainless steel powder (thickener, 325 mesh (44 μm)) was added to the paste and mixed under the same conditions. Finally, 4.73 g of stainless steel wire (3 mm x 2 μm, thickener) was added to the paste, hand mixed with a spatula for 1 minute, and then mixed in a FlackTek® mixer at 2300 rpm for 1 minute.

[0137] Preparation of a composite material containing 7.7% by volume of gallium alloy (paste) A Sylgard™ 184 thin film was produced using the film preparation procedure described in Comparative Example C-6. Once the film was cured, 1.82 g of the gallium-based paste prepared above in this example was uniformly spread onto the 1.5" x 1.5" cured film. To completely encapsulate the laminate composite, an additional 3 g of a mixture of Sylgard™ Part A and Part B was cast onto the gallium-based paste and heat cured at 100°C for 45 minutes. The resulting product was a 1.5" x 1.5" laminated film composite.

[0138] Example 3 Preparation of paste 25.83 g of gallium alloy (Indalloy® 46L) and 1.07 g of Triton™ X100 were mixed in a FlackTek centrifugal planetary mixer at 2300 rpm for 1 minute.

[0139] Fabrication of laminated composite material containing 14.1% by volume of gallium alloy (paste) A thin Nusil 5860 film was produced using the film preparation procedure described in Comparative Example C-5. Once the film was cured, 0.59 g of the gallium-based paste prepared above in this example was uniformly applied onto the 1.5" x 1.5" cured film. After repeating the film preparation of Comparative Example C-5, 5 g of a mixture of Nusil 5860 Part A and Part B was dissolved in 5 g of THF. The resulting polymer solution was cast onto the gallium-based paste and thermally cured at 100°C for 2 hours after most of the THF solvent had evaporated (approximately 18 hours / overnight). The resulting product was a 1.5" x 1.5" laminated film composite.

[0140] Example 4 Thermal aging The comparative example C-5 film and the laminated films produced in Examples 1 to 3 were placed in an oven at 100° C. for 10 days to evaluate the conductive performance and / or elongation.

[0141] After curing, the composites described in Comparative Examples C-1, C-2, and C-3 could be easily handled and cut into dog bone shapes for mechanical testing.

[0142] The tensile properties (elongation and immediate break stress) of the thermoplastic polyurethane control and the composites containing the gallium-based paste are summarized in Table 1 below. Suitable equipment for measuring these properties is commercially available from Instron, Inc., Norwood, Massachusetts, USA.

[0143] These composites clearly demonstrate the sensitivity of polymeric elastic compositions to the degree of gallium alloy loading, and clearly demonstrate that the methods and compositions disclosed herein result in composites that exhibit excellent elastic properties in combination with high metal loading.

[0144] [Table 2]

[0145] Table 1 clearly shows that the membrane of Comparative Example C-5 does not exhibit degradation of mechanical properties with aging.

[0146] Table 2 summarizes the conductivity values, determined as attenuation in dB / mm, for composites made according to Comparative Example C-1, Comparative Example C-2, Comparative Example C-3, Example 1, Example 2, and Example 3. All reported attenuation results have been normalized to eliminate sample thickness as a variable.

[0147] To determine the attenuation, a full two-port measurement is used on an X-band waveguide covering 8-12 GHz. The composite sample is compressed between two X-band waveguides connected to a Keysight N5245A network analyzer via a waveguide-to-coaxial cable transition. A full two-port calibration is performed using an empty waveguide as a through standard. The empty waveguide measurement is saved to remove the waveguide loss in post-processing. Some samples are first measured with a center cutout identical to the waveguide opening to ensure a proper electrical seal and to determine the amount of loss due to high frequency leakage, then another measurement is made on a full rectangular sample. Other samples are measured as is.

[0148] Moving from organic to inorganic thickeners improved attenuation. The combination of inorganic particles and anisotropic metal wires resulted in the highest conductivity (-16 dB / mm) among non-laminated composites.

[0149] Example 2, a laminate containing both a stainless steel powder thickener and micron-sized linear additives in addition to the compatibilizer, produced an attenuation of -29 dB / mm with only about 7.7 volume percent gallium alloy, demonstrating the high electrical conductivity achieved by the disclosed conductive composites using relatively low loadings of low melting conductors.

[0150] The laminate composites of Examples 1 and 2 were heat aged in air at 100° C. for 10 days and showed no loss in electrical conductivity.

[0151] [Table 3]

[0152] Although the conductive composite material and the method of making the conductive composite material have been described in detail with reference to specific examples, it is apparent that modifications and variations are possible without departing from the scope of the appended claims. More specifically, although certain aspects of the present disclosure are identified herein as being particularly advantageous, the present disclosure is not necessarily limited to these specific aspects.

[0153] Additionally, this disclosure includes examples according to the following provisions:

[0154] Clause 1.(a) a polymer; (b) a conductor selected from metals and metal alloys having a melting temperature of less than about 60° C.; (c) a compatibilizer; 1. An electrically conductive composite material comprising:

[0155] Clause 2. The conductive composite material of clause 1, wherein the compatibilizer comprises a non-ionic amphiphilic compound, an ionic amphiphilic compound, metal nanoparticles, or a mixture thereof.

[0156] Clause 3. The conductive composite material of clause 2, wherein the metal nanoparticles have a particle size of less than 100 nm in a linear dimension and comprise copper, nickel, stainless steel, tin, titanium, tungsten, mixtures thereof, or alloys thereof.

[0157] Clause 4. The conductive composite material according to clause 2 or 3, wherein the non-ionic amphiphilic compound is selected from the group consisting of fatty alcohol ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethoxylated amines, fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, alkyl polyglucosides, fatty amine oxides, sulfoxides, organophosphine oxides, and mixtures thereof.

[0158] Clause 5. The conductive composite material according to any one of clauses 2 to 4, wherein the non-ionic amphiphilic compound is a surfactant.

[0159] Clause 6. The conductive composite material of any one of clauses 1 to 5, wherein the polymer comprises a thermoset polymer or a thermoplastic polymer.

[0160] Clause 7. The conductive composite material of any one of clauses 1 to 5, wherein the polymer comprises polyamide, polylactic acid, polystyrene, acrylonitrile-butadiene-styrene, polybenzimidazole, polycarbonate, polyethersulfone, polyoxymethylene, polyaryletherketone, polyetherimide, polyethylene, polypropylene, polyphenylene oxide, polyphenylene sulfide, polyvinyl chloride, polyester, polyvinylidene fluoride, silicone, perfluoropolyether, polybutadiene, polyacrylate, polyetherimide, polyurethane, polyurea / polyurethane hybrid, thermoplastic vulcanizate, polytetrafluoroethylene, polyepoxide, polyimide, cyanate ester, polycyanurate, polysulfide, or copolymers or mixtures thereof.

[0161] Clause 8. The conductive composite material of any one of clauses 1 to 5, wherein the conductor is an alloy containing at least about 50% by weight of gallium, bismuth, mercury or a combination thereof.

[0162] Clause 9. The conductive composite material of clause 8, wherein the alloy further contains indium, tin, phosphorus, lead, zinc, cadmium, antimony or a combination thereof.

[0163] Clause 10. The conductive composite material according to any one of clauses 1 to 9, wherein the conductor is an alloy containing indium and 50 to 97% by weight of gallium.

[0164] Clause 11. The conductive composite material of any one of clauses 1 to 10, wherein the conductor is an alloy containing about 15-30% by weight indium, about 55-80% by weight gallium, and at least one metal selected from tin and zinc.

[0165] Clause 12. The conductive composite material of any one of clauses 1 to 11, further comprising a thickener.

[0166] Clause 13. The conductive composite material according to clause 12, wherein the thickener is an organic thickener.

[0167] Clause 14. The conductive composite material according to clause 12, wherein the thickener is maltol, carbon, phenol, naphthalene, 1-naphthol, 2-naphthol or 4-pyridone.

[0168] Clause 15. The conductive composite material according to clause 12, wherein the thickener is an inorganic thickener.

[0169] Clause 16. The thickener comprises rod-shaped particles, filamentous particles, substantially spherical particles or mixtures thereof, and comprises a metal selected from nickel, titanium, tungsten, stainless steel, copper and tin, a metal oxide of nickel, titanium, tungsten, stainless steel, copper, tin or zinc, a ceramic, or a combination thereof; 13. The conductive composite material of claim 12, wherein the substantially spherical particles have an average particle size of about 0.1-500 μm, and the rod-shaped and filamentary particles have a length of 0.01-10 mm.

[0170] Clause 17. The conductive composite material of any one of clauses 1 to 16, comprising about 0.1 to 50 volume percent of the conductor.

[0171] Clause 18. The conductive composite material according to any one of clauses 1 to 17, which is a laminate.

[0172] Clause 19. The conductive composite of clause 18, wherein the conductor and the compatibilizer are substantially uniformly mixed and form a layer of a laminate.

[0173] Clause 20. The conductive composite material of any one of clauses 1 to 17, wherein the conductor and the compatibilizer are substantially uniformly dispersed throughout the polymer.

[0174] Clause 21. The conductive composite material of clause 20, wherein the conductor is continuously entrapped within the polymer in the form of a network comprising the conductor and the compatibilizer.

[0175] Article 22. At 20°C, approximately 5 x 10 5 22. The conductive composite material of any one of the preceding clauses, having a bulk conductivity of less than or equal to S / m, an elongation of greater than or equal to 50%, and a tensile strength of greater than or equal to 3 MPa.

[0176] Clause 23. The conductive composite material of any one of clauses 1 to 22, having a density of about 1 to 30 g / cc.

[0177] Clause 24. The conductive composite material of any one of clauses 1 to 23, having a density of less than 7 g / cc.

[0178] Clause 25. The conductive composite material according to any one of clauses 1 to 24, further comprising an additive that improves thermo-oxidative stability.

[0179] Clause 26. The conductive composite material according to clause 25, wherein the additive is phosphorus, iron oxide, a phenolic antioxidant, a metal passivator, or a combination thereof.

[0180] Clause 27. A composition comprising a metal or metal alloy having a melting temperature of less than 60°C and a compatibilizer.

[0181] Clause 28. The composition of clause 27, wherein the compatibilizer comprises a non-ionic amphiphilic compound, an ionic amphiphilic compound, a metal nanoparticle, or a mixture thereof.

[0182] Clause 29. The composition according to clause 27 or 28, further comprising an inorganic or organic thickener.

[0183] Clause 30. The composition of clause 29, wherein the inorganic thickener is a particle of the inorganic thickener that is substantially spherical or has an aspect ratio of greater than about 2.

[0184] Clause 31. The composition according to clause 30, wherein the particles of the inorganic thickener are substantially spherical and have a diameter of about 0.1 to 500 μm.

[0185] Clause 32. The composition of clause 29, wherein the inorganic thickener is a particle of inorganic thickener having an aspect ratio of greater than about 2 and a length of about 0.01 to 10 mm.

[0186] Clause 33. The composition of any one of clauses 27 to 32, which is a paste having a loss modulus (G'') greater than the storage modulus (G').

[0187] Clause 34. A method of making a conductive composite material, comprising the steps of mixing a monomer mixture or a polymer composition with (a) a conductor selected from metals and metal alloys having a melting temperature of less than about 60° C., and (b) a compatibilizer.

[0188] Clause 35. The method of clause 34, further comprising curing the monomer mixture to form a conductive composite material.

[0189] Clause 36. A method of making a conductive composite material, comprising: layering a conductive paste on a surface of a first polymer, the conductive paste comprising: (a) a conductor selected from metals and metal alloys having a melting temperature of less than about 60° C.; and (b) a compatibilizer.

[0190] Clause 37. The method of clause 36, further comprising the step of applying a layer of a second polymer to a surface of the first polymer having the conductive paste.

[0191] Clause 38. The method of clause 37, wherein the second polymer is of the same type or of a different type as the first polymer.

[0192] Clause 39. Elastomers; a conductor selected from metals and metal alloys having a melting temperature of less than 60° C.; and a compatibilizer, At 20°C, approximately 5 x 10 5 Bulk electrical conductivity of 0.01 S / m or less, elongation of 0.01% or more, and tensile strength of 0.01 MPa or more. Conductive composite material.

[0193] Clause 40. A substrate carrying a layer of the conductive composite material according to any one of clauses 1 to 26 or 39.

[0194] Clause 41. A method of producing a substrate carrying a layer of a conductive composite material, the method comprising the steps of heating a conductive composite material described in any one of clauses 1 to 26 or 39, and applying the conductive composite material to a substrate.

Claims

1. (a) a polymer; (b) a conductor selected from a metal alloy having a melting temperature of less than 60° C.; (c) a compatibilizer; Including, the conductor is an alloy containing at least 50% by weight of gallium, bismuth, mercury, or a combination thereof; The compatibilizer comprises a non-ionic amphiphilic compound; Conductive composite material.

2. the compatibilizer further comprises an ionic amphiphilic compound, a metal nanoparticle, or a mixture thereof; 10. The conductive composite of claim 1, wherein the metal nanoparticles have a particle size of less than 100 nm in a linear dimension and comprise copper, nickel, stainless steel, tin, titanium, tungsten, mixtures thereof, or alloys thereof.

3. 2. The conductive composite of claim 1, wherein the non-ionic amphiphilic compound is selected from the group consisting of fatty alcohol ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethoxylated amines, fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, alkyl polyglucosides, fatty amine oxides, sulfoxides, organophosphine oxides, and mixtures thereof.

4. The conductive composite of claim 1 , wherein the polymer comprises a thermoset polymer or a thermoplastic polymer.

5. Further comprising a thickener, 2. The conductive composite material of claim 1, wherein the thickener is substantially spherical particles of an inorganic thickener having an average particle size of 0.1 to 500 μm, rod-shaped or linear particles of an inorganic thickener having an aspect ratio greater than 2 and a length of 0.01 to 10 mm, substantially spherical particles of an organic thickener having an average particle size of 0.1 to 500 μm, or a mixture thereof.

6. The conductive composite of claim 5 , wherein the thickener is an organic thickener.

7. The conductive composite of claim 5 , wherein the thickener is an inorganic thickener.

8. Further comprising a thickener, 2. The conductive composite material of claim 1, wherein the thickener comprises rod-shaped particles, linear particles, substantially spherical particles or a mixture thereof and comprises a metal selected from nickel, titanium, tungsten, stainless steel, copper and tin, a metal oxide of nickel, titanium, tungsten, stainless steel, copper, tin or zinc, a ceramic, or a combination thereof, wherein the substantially spherical particles have an average particle size of 0.1 to 500 μm, and the rod-shaped particles and linear particles have a length of 0.01 to 10 mm.

9. The conductive composite material of claim 1, comprising 0.1 to 50 volume percent of the conductor.

10. The conductive composite of claim 1 which is a laminate.

11. 11. The conductive composite of claim 10, wherein the conductor and the compatibilizer are substantially uniformly mixed and form a layer of the laminate.

12. The conductive composite of claim 1 , wherein the conductor and the compatibilizer are substantially uniformly dispersed throughout the polymer.

13. 5 x 10 at 20°C 5 10. The conductive composite of claim 1 having a bulk conductivity of 0.1 S / m or less, an elongation of 50% or more, and a tensile strength of 3 MPa or more.

14. 10. The conductive composite of claim 1, further comprising an additive that improves thermo-oxidative stability.

15. a conductor selected from a metal alloy having a melting temperature of less than 60° C.; and a compatibilizer; the conductor is an alloy containing at least 50% by weight of gallium, bismuth, mercury, or a combination thereof; A composition wherein the compatibilizer comprises a non-ionic amphiphilic compound.

16. Further comprising a thickener, 16. The composition of claim 15, wherein the thickener is substantially spherical particles of an inorganic thickener having an average particle size of 0.1 to 500 μm, rod-shaped or linear particles of an inorganic thickener having an aspect ratio greater than 2 and a length of 0.01 to 10 mm, substantially spherical particles of an organic thickener having an average particle size of 0.1 to 500 μm, or a mixture thereof.

17. Mixing the monomer mixture or polymer composition with (a) a conductor selected from a metal alloy having a melting temperature below 60° C., and (b) a compatibilizer, or layering a conductive paste comprising (a) a conductor selected from a metal alloy having a melting temperature below 60° C., and (b) a compatibilizer, on the surface of the first polymer. Including, the conductor is an alloy containing at least 50% by weight of gallium, bismuth, mercury, or a combination thereof; The method of making a conductive composite material, wherein the compatibilizer comprises a non-ionic amphiphilic compound.

18. A substrate carrying a layer of the conductive composite material of claim 1.

19. 13. A method of making a substrate carrying a layer of a conductive composite material, comprising the steps of heating the conductive composite material of claim 1 and applying the conductive composite material to a substrate.

Citation Information

Patent Citations

  • Liquid-state metal electronic paste and preparation method thereof

    CN107452436A

  • Alkaline battery and negative electrode active material thereof

    JP1990086064A

  • Alkaline battery and negative electrode active substance thereof

    JP1990087464A

  • Multilayered separated liquid substrate

    JP1998130125A

  • Conductive composites

    JP2019112615A